Generalizing survey results from student samples: Implications from service recovery research - Ok, Chihyung; Shanklin, Carol W.; Back, Ki-Joon (My University, 2008)
Using college students as research subjects in consumer research may or may not be appropriate. This paper discusses external validity of research findings using student subjects as surrogates for consumers in experimental, particularly scenario based, studies. A study that investigated differences between a student sample and a customer sample in response to service experience is described. Results were mixed. No significant mean differences were found in complaint intention, preference to complain to an employee or a manager, overall satisfaction, and revisit intention toward service providers. However, significant discrepancies were observed in testing the role of initial overall satisfaction in evaluating recovery satisfaction and in the relative importance of dimensions of justice. For both student and non-student groups, regardless their recovery satisfaction were positive or negative, initial overall satisfaction was a stronger predictor for post-recovery overall satisfaction than recovery satisfaction.
Keywords: Generalizability; Student sample; Complaint intentions; Service recovery; Satisfaction